HEALTHCARE DATA SECURITY: SAFEGUARDING PATIENT INFORMATION IN THE DIGITAL AGE - Reshma Vemula, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
Healthcare organizations face mounting cybersecurity challenges as they transition to electronic health records. This article examines how healthcare providers can protect sensitive patient information through multi-layered security architectures, robust access controls, and advanced threat detection systems. The analysis demonstrates that effective security measures enhance operational efficiency, strengthen patient trust, and enable technological innovation in healthcare delivery while maintaining HIPAA compliance.